Functioning Peculiarities of the Eponymic Terms in Mass-media (Linguostylistic Studies, 2021)
The article analyzes the lexical and semantic features of eponymous terms in Ukrainian mass-media texts. The study focuses on the stylistic functions of terms which include proper names in the language of the media. The research material includes eponymous terms of the Ukrainian language considered in their function of reflecting social reality in media publications. The research was carried out on the basis of the General Regionally Annotated Corpus of Ukrainian, which contains written texts in Ukrainian from different regions of Ukraine and other countries. The change of lexical-semantic and stylistic characteristics of a language sign in the process of its terminologization and determinologization is traced in terms of the pattern: actual onym – term-appellative in scientific style – term in non-special (media) context.An eponymous term, outside its terminological system, can be used in the language of the media in the literal sense or can change its semantic content depending on extralinguistic factors. Cases of re-using the eponym as a unit of onomastics to name another object indicate the potential possibility of the anthropological component of the eponymous term to create the preconditions for its use outside the terminological system.Frequently, in the media text, deterministic eponyms are used in the meaning inherent for the conversational style, which is an example of stylistic convergence. Not only does the semantic content acquire the stylistic coloring characteristic for the colloquial discourse, but also the eponymous linguistic sign changes, undergoing metaphorical re-thinking. The study has revealed that eponymous terms, having come out of the onomastic field, again become a part of the onomastic unit and function in this sense in the newspaper text. Thus, the linguistic sign undergoes a multi-stage semantic transformation: the surname of the scientist → the term → the nickname of the person. In media texts, side by side with commonly used deterministic eponyms, the eponymous name is used as a form, a template, a word combination with a proper name-component, which traditionally denotes authorship or involvement in the nominated reality.The key finding of the study argues that eponymous terms in the media text actualize their implicit function as signs of culture. It leads to their widespread use, as they emphasize the role of their country's representatives in the development of scientific thought.
Keywords: language of media; mass media texts; eponyms; genres of journalism; onomastics